2017
DOI: 10.1016/s1878-6480(17)30373-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low doses of esmolol on cardiac and vascular function in experimental septic shock

Abstract: Background: Administration of a selective β1-blocker, such as esmolol, in human septic shock has demonstrated cardiovascular protective effects related to heart rate reduction. Certain experimental data also indicate that esmolol exerts systemic anti-inflammatory and beneficial effects on vascular tone. Thus, the present study aimed to determine whether a non-chronotropic dose of esmolol maintains its protective cardiovascular and anti-inflammatory effects in experimental septic shock. Methods: Four hours afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Beside this immune rebalancing in experimental mid-grade sepsis, it is important to reiterate that β 1 -AR blockade also has major cardiovascular effects. In agreement with most other experimental or clinical studies, septic mice receiving β-AR blockade showed no alteration in cardiac power, despite a decrease in HR, suggesting improved cardiac efficiency (10, 15, 44, 50). However, it should be borne in mind that animals only received an initial subcutaneous bolus of fluid resuscitation and no fluids nor catecholamines thereafter.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Beside this immune rebalancing in experimental mid-grade sepsis, it is important to reiterate that β 1 -AR blockade also has major cardiovascular effects. In agreement with most other experimental or clinical studies, septic mice receiving β-AR blockade showed no alteration in cardiac power, despite a decrease in HR, suggesting improved cardiac efficiency (10, 15, 44, 50). However, it should be borne in mind that animals only received an initial subcutaneous bolus of fluid resuscitation and no fluids nor catecholamines thereafter.…”
Section: Discussionsupporting
confidence: 91%
“…In numerous conditions, such as acute heart failure, burn injuries, and septic shock, β 1 -AR blockade has been consistently associated with protective effects on inflammation and hemodynamics (15, 42, 43). As others, we too found a global decrease in pro- and anti-inflammatory mediators in animals with mid-grade sepsis treated by β 1 -AR blockade (15, 44, 45). Underlying mechanisms are still not elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Esmolol, as an ultra-short-acting selective β 1 receptor blocker, has been confirmed, at home and abroad, to have cardiac protective effect, and to reduce the hospitalization rate and mortality of septic patients with cardiac dysfunction [18] [19]. The results of animal experiments also confirmed that it could reverse left ventricular hypertrophy [20].…”
Section: Introductionmentioning
confidence: 98%